Chilling Stress Triggers VvAgo1-Mediated miRNA-Like RNA Biogenesis in Volvariella volvacea - Gong, Ming; Wang, Ying; Zhang, Jinsong; Zhao, Yan; Wan, Jianing; Shang, Junjun; Yang, Ruiheng; Wu, Yingying; Li, Yan; Tan, Qi; Bao, Dapeng (Frontiers in Microbiology, 2020)
In Volvariella volvacea, an important species of edible mushroom, cryogenic autolysis is a typical phenomenon that occurs during abnormal metabolism. Analysis of gene expression profiling and qPCR showed that chilling stress (CS) significantly and continuously upregulated only one type of Argonaute in V. volvacea, i.e., VvAgo1. Structural and evolutionary analysis revealed that VvAgo1 belongs to the Ago-like family, and its evolution has involved gene duplication, subsequent gene loss, and purifying selection. Analysis of its interaction network and expression suggested that CS triggers VvAgo1-mediated miRNA-like RNA (milRNA) biogenesis in V. volvacea V23 but not in VH3 (a composite mutant strain from V23 with improved CS resistance). Small RNA sequencing and qPCR analysis confirmed that CS triggered the increased milRNA expression in V23 and not in VH3. The predicted target genes of the increased milRNAs were enriched in several pathways, such as signal transduction and ubiquitination. Heatmap analysis showed that CS altered the expression profile of milRNAs with their target genes related to signal transduction and ubiquitination in V23. Combined analysis of transcriptome and proteome data confirmed that most of the target genes of the increased milRNAs were not translated into proteins. Our observations indicate that CS might trigger VvAgo1-mediated RNAi to facilitate the cryogenic autolysis of V. volvacea.